Consumers' lifestyle of health and sustainability as determining factor of purchase behaviour for sustainable products: an empirical analysis. (16th July 2021) - Matharu, Manita; Jain, Ruchi; Kamboj, Shampy
Sustainability and environmentally conscious behaviour towards sustainable products are emerging research areas in India. There is dearth of research to understand Indian consumers' sustainable purchase behaviour, particularly in the context of consumers' lifestyle. The present study aims to examine the effect of consumer lifestyle of health and sustainability (LOHAS) on purchase behaviour. This paper adapts LOHAS, consumer attitude towards sustainable purchasing, subjective norm, willingness to pay premium for sustainable product to examine sustainable product purchase behaviour in Indian context through an extended theory of planned behaviour. Collection of data is done through a questionnaire filled from 316 individuals who are consumers of sustainable products. This study validated the proposed conceptual model by structured equation modelling and provides that LOHAS emerged as an antecedent to consumer attitudes towards sustainable product purchase. Additionally, attitude towards sustainable purchasing and willingness to pay price for sustainable products found to be significant determinants of consumers' sustainable purchase behaviour. The findings of this paper might interest consumer behaviour scholars and those firms that concern regarding the consumers purchase behaviour for sustainable products.